Effect of hydroxyapatite and tricalcium phosphate addition on protein foaming-consolidation porous alumina - Iis, Sopyan; ., Ahmad Fadli; Mel, Maizirwan (Springer Netherlands, 2012)
Porous alumina-hydroxyapatite (HA) and alumina- tricalcium phosphate (TCP) composites have been fabricated to investigate the effect of HA and b-TCP addition on protein foaming-consolidation derived porous alumina. HA and b-TCP loadings along with yolk content, starch content, and sintering temperature were varied to modulate performance of the porous composites. The rheological behavior of slurry shifted from pseudoplastic flow to a Newtonian fluid with increasing yolk concentration. The foaming capacity of slurry increased with yolk addition. The addition of starch into slurry resulted in bigger pore size and avoided the porous bodies from cracks. The shrinkage of sintered bodies increased with increasing HA loading, but decreased with increasing b-TCP loading. The compressive strength of porous alumina- HA body was found 2.9 MPa at 45.8% porosity and 20.4 MPa at 36.8% porosity. The increasing porosity of porous alumina-TCP body from 56.1 to 61.6% improved the compressive strength from 3.1 to 4.2 MPa. Increasing sintering temperature resulted in large grain size among powder particles, thus improving the compressive strength of porous bodies. Preliminary results of DF-1 cells culture on the surface of porous alumina and alumina-TCP samples are also reported.